Jean Prouvé : la Maison tropicale = [Jean Prouvé]. the tropical house - Prouvé, Jean (Centre Pompidou, 2009)
Habitations démontables et maisons usinées dans le production des Ateliers Jean Prouvé=Portable and demountable dwellings, and manufactured homes produced by the Ateliers Jean Prouvé / Olivier Cinquiabre -- La Maison tropicale=The Tropical House / Oli